جوانب الغلو والتكفير في الفكر السلفي المعاصر - علي، علي محمد حسن (جامعة الأزهر - كلية أصول الدين والدعوة بالزقازيق, 2021)
هدفت الدراسة لبيان جوانب الغلو والتكفير في الفكر السلفي المعاصر، وبخاصة في مجال التوحيد، وقد استخدم الباحث عدة مناهج بحثية هي: المنهج التحليلي، والمنهج المقارن، والمنهج النقدي، وكان تقسيم البحث على هذا النحو: المبحث الأول: وجاء بعنوان (التعريف بأهم المصطلحات الواردة بالبحث وهي: الغلو، التكفير، السلف)، وتضمن التعريف بها لغوياً واصطلاحياً، والآيات والأحاديث الدالة على التحذير من الغلو، والتكفير، ثم بيان معنى مصطلح السلف وكونه يطلق فقط على أهل القرون الثلاثة المتقدمة كما نص حديث رسول الله صلى الله عليه وسلم على ذلك. المبحث الثاني: وهو بعنوان (تكفير من سمى التوحيد اعتقاداً، ومن لم يقسم التوحيد إلى ثلاثة أقسام (عرض ونقد)، وهذا المبحث جاء مشتملاً على تقسيم التوحيد لثلاثة أقسام هي: توحيد الربوبية، وتوحيد الألوهية، وتوحيد الأسماء والصفات، وقد زعم من قسموا التوحيد لهذه الأقسام أن المشركين كانوا يقرون بتوحيد الربوبية، وأيضاً فضلوا المشركين على كثير من المسلمين في زماننا المعاصر، وفيه أيضاً ظهور نوع جديد من التوحيد يسمى بتوحيد الحاكمية، وقد تضمن هذا المبحث عرض التقسيم على القرآن الكريم، وبيان المراد من الآيات التي توهم إقرار المشركين بتوحيد الربوبية، ثم بيان معتقد الأشاعرة في قضية التوحيد، ومناقشة أصحاب هذه الدعوى مناقشة موضوعية بعيدة عن التعصب، وبيان تناقض من قالوا بإقرار المشركين بتوحيد الربوبية، ثم خاتمة البحث، وفيها: أبرز أهم التوصيات والمقترحات، وأهم النتائج التي توصل إليها الباحث، ثم قائمة المراجع.
The study aims at illustrating the aspects of exaggeration and Takfir in contemporary Salafi thought, especially in the field of monotheism. The researcher used several research methods: the analytical approach, the comparative approach, and the critical approach. The research division is as follows: The first subject of research is entitled (definition of the most important terms mentioned in the research i.e. Exaggeration, Takfir, and Salaf). It included the definition of these terms linguistically and idiomatically, Qur'anic verses and Prophetic Haidths that warn about exaggeration and Takfir, and illustrating the meaning of the term "Salaf" and that it only refers to the people of the first three centuries after Hijra, as mentioned in the prophetic hadith. The second subject of research is entitled (Takfir of those who confined monotheism to belief and those who do not divide monotheism into three sections (a discussion and criticism). This part includes dividing monotheism into three sections: the oneness of the Lord, Unity of Worship, and names and attributes of God. Those who believe in this division claimed that polytheists believed in the oneness of the Lord. They also preferred polytheists to many contemporary Muslims. This second subject also includes the emergence of a new type of monotheism called "Al Hakemeya" i.e. the Dominion of Allah. It also includes discussing the above-mentioned division in the light of the Holy Qur'an and illustrating what is meant by the verses that give the impression that polytheists believe in the oneness of the Lord. Then, it illustrates the Ash`ari's belief in regard to monotheism and discussing them objectively without Sectarianism. Clarifying the contradiction of those who say that polytheists believe in the oneness of the Lord is also included. Finally comes the conclusion of the research, including the most important recommendations and proposals, the most important conclusions of the researcher, and bibliography.
Keywords: الغلو -- التكفير -- السلفية -- الفكر السلفي -- التوحيد